L’Islam: un pensiero diverso sulla realtà umana - Carnevali, Rossella; Fiori Nastro, Paolo (Il sogno della farfalla, 2007)
This article explores how the Islamic world views the mental reality of human beings, pointing out the strong differences that emerge when compared to the Western world. The authors compare the Bible and the Koran, analyze a number of written sources and interview people of Islamic origin. It becomes evident that the West has always been influenced by the belief that original sin exists and therefore man is an innately wicked creature. This leads one to think that the reality of humans is one of scission and of conflict between good and evil, corresponding respectively to reason and irrationality. This type of thinking, evidently, does not allow us to carry out research into the human mind. In the Koran, instead, original sin is forgiven, and human reality is not viewed as split, offering the Islamic world the premises for carrying out research into the mental reality of humans, something, however, it has not done.